Galactosaemia: a new severe variant due to uridine diphosphate galactose-4-epimerase deficiency. Issue 11 (November 1981) - Holton, J B; Gillett, M G; MacFaul, R; Young, R
Abstract : A baby presented on day 5 with symptoms of classical galactosaemia which are believed to be owing to a lack of uridine diphosphate-4-epimerase, rather than to the usual galactose-1-phosphate uridyl transferase defect. Apart from galactosaemia the condition was characterised biochemically by a red cell accumulation of galactose-1-phosphate and uridine diphosphate galactose. Galactose restriction modified the acute clinical and biochemical abnormality, but it appears essential to include some galactose in the diet in this condition to allow synthesis of galactosides, including the brain gangliosides.